PENANGGULANGAN PATOLOGI BIROKRASI DI KANTOR KECAMATAN LAPPARIAJA KABUPATEN BONE - Almahdali, Humairah; Sakir, Ahmad Rosandi (Holistik Analisis Nexus, 2024)
The conclusion of this study indicates that the implementation of offensive and defensive strategies in the Sub-District Office has proceeded adequately. Evaluation of offensive strategy indicators, such as the approach among colleagues, shows a significant improvement. Although it is already quite good, further improvement is necessary, especially in terms of employees giving warnings to colleagues who violate rules. The family approach has also positively contributed to efforts to prevent bureaucratic pathologies. The weekly evaluations conducted by the section head with the team can be seen as a proactive step in maintaining performance quality. Although it is already quite good, there is a need for improvement to make these evaluations more effective in preventing and addressing violations. On the defensive strategy side, implementing mild sanctions in the form of written warnings has been effective. These sanctions are given to employees who violate rules, such as being absent without notice for 6 to 10 days. Moderate and severe sanctions have also been well implemented when needed, indicating readiness to respond to more serious violations. Overall, offensive and defensive strategies in the Sub-District Office of Pitumpanua are already quite good, but continuous improvement is needed to ensure their effectiveness in dealing with various situations and cases of bureaucratic pathologies in the future.